On the silver jubilee of crustacean antimicrobial peptides. (12th September 2021) - Matos, Gabriel Machado; Rosa, Rafael Diego
Abstract: Antimicrobial peptides (AMPs) are widely distributed effector molecules that provide a first line of defence for organisms that lack adaptive immunity, such as crustaceans. They also represent bioactive molecules with great potential as therapeutic agents in aquaculture and biomedicine. Over the last years, an intensive research effort has been devoted to the identification and characterisation of antimicrobials in crustaceans resulting in the recognition of twelve gene‐encoded AMP families to date. In addition to classical linear and multi‐domain AMPs, crustaceans also rely on the production of unconventional ones, such as lysozymes and AMPs encrypted in large proteins carrying nonimmune functions. Besides their molecular and functional diversity, crustaceans have a particular AMP repertoire usually composed of diverse multigene families of taxonomically restricted peptides/polypeptides. In fact, only a few families of AMPs are shared between crustaceans and their close arthropod relatives. This review celebrates the silver jubilee of the discovery of the first crustacean AMPs and presents an updated and comprehensive overview in terms of structure, diversity and biological properties, emphasising their role in immune responses and in host‐microbe interactions. We also discuss the main progress achieved so far and major challenges remaining.